Blunted heart rate reserve with dobutamine stress echocardiography predicts outcome in diabetes and/or chronic kidney disease. (14th October 2021) - Bellagamba, C.C.A; Quevedo, N.M; Torres, M
Abstract: Background: A blunted heart rate reserve (HRR) during dobutamine stress echo (DSE) is an index of the altered cardiac sympathetic reserve, which is frequently present in diabetes mellitus (DM) or chronic kidney disease (CKD). Aim: To assess the prognostic value of HRR during DSE. Methods: We recruited 280 patients (mean age 62.9±13.1 years; 128 (45.7%) male; 28.2% on beta-blockers at the time of testing) who underwent DSE for known or suspected coronary artery disease and/or heart failure and were followed-up. Four subsets were identified: Group 1 (111 pts without DM or CKD); group 2 (37 with DM without CKD); group 3 (90 with CKD with or without DM); and group 4 (42 with CKD on dialysis). HRR was calculated by EKG as the peak/rest HR ratio. Results: Ischemia was identified in 34/280 (12.1%) pts. During a median follow-up time of 40.3±30.5 months, 120 events occurred: 46 deaths, 15 non-fatal myocardial infarctions, 23 hospital admissions for acute decompensated heart failure, and 36 myocardial revascularizations. Multivariable comparison of HRR among the 4 groups using post hoc test showed a blunted HRR in group 3 (1.66±0.32) and 4 (1.65±0.27) when compared with group 1 (HRR 1.85±0.35), p<0.01. Group 2 (1.73±0.28) was not different from any group (p=ns). Groups 3 and 4 were not different between them (p=ns). A post hoc Tukey test for HRR separated in tercils, 1st: HRR <1.59, 2nd: 1.59 < HRR <1.86 and 3rd: HRR >1.86 (p<0.000). Kaplan-Meier curves showed blunted HRR as an independent predictor of event-free survival in the overall group - 1st: 66.08±5.9 months, 95% CI 54.3–77.7; 2nd: 69.52±6.5, 95% CI 56.6–82.3; 3rd: 90.05±5.3, 95% CI 79.5–100.5. See Figure. HRR was comparable in patients with and without inducible ischemia and off or on beta-blockers. Conclusion: A blunted HRR during DSE is frequent in patients with DM and CKD, independent of inducible ischemia and use of beta-blockers, and is a useful non-imaging predictor of adverse events. Funding Acknowledgement: Type of funding sources: None.